ANALISIS PERSISTENSI LABA PERSPEKTIF ARUS KAS OPERASI DAN TINGKAT HUTANG PADA PERUSAHAAN SEKTOR KEUANGAN DI INDONESIA - Yenni Cahyani; Suciati Muanifah (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
Various ways are used to increase profits, because the company realizes that there are many things that can be done with profits, including the existence of the business in the future. Several financial instruments, which are considered to determine the persistence of earnings are operating cash flows and debt levels. The two instruments describe the current and future earnings conditions, so they need to be taken seriously. Therefore, this research was conducted, to try to estimate the possibility of increasing earnings persistence based on cash flow and debt instruments. In carrying out scientific evidence, this research determines quantitative as the fundamental analysis, using the causal method, so that the estimated value is obtained. The research data is secondary, obtained from the financial statements of 17 financial sub-sector companies listed on the Indonesian stock exchange. The financial report data used were 102 (2015-2020 period), based on the determination of a number of criteria (purposive), then analyzed using panel data regression statistics. The results showed that earnings persistence would increase maximally in the simultaneous model, amounting to 27.61%. This means that optimizing operating cash flow and controlling debt are options for companies to increase earnings persistence, which in turn can increase the value of the company in the future.